Wielka Brytania wobec kształtowania się amerykańskiej polityki „otwartych drzwi” w Chinach (1898–1900) - Pajor, Jan (Acta Universitatis Lodziensis. Folia Historica, 2012)
The intention of this paper is to present how the British idea of the Open Door in China permeated to the United States and influenced the diplomatic actions of this country. Another matter covered here is Whitehall’s reaction to the first and second series of the Open Door notes, issued by the Department of State. The Open Door doctrine, encompassing the principles of equal commercial treatment and maintenance of China’s territorial integrity, was for many years one of the pillars of the British Far Eastern policy. However, when in the aftermath of China’s severe defeat in war with Japan foreign Powers engaged in creating spheres of influence in the Middle Kingdom, Great Britain diverged from its traditional position. London, having commercial preponderance in China, was at first against the dismemberment of this country, but eventually – since its endeavours to gain support of other Powers for the Open Door policy proved abortive – decided to perpetuate its sphere of influence. The United States, approached by the British in March 1898, were unwilling to act at that time, nor did they want to align with anyone. Nevertheless, soon afterwards the concept of the Open Door started gaining popularity among American politicians mainly due to various British influences. Therefore at the turn of 1898 and 1899 London reiterated its proposition to cooperate in China, but was rejected. The United States were determined to act alone and between 1899 and 1900 issued two series of the Open Door notes. Whilst Great Britain cordially applauded these pronouncements in general, she tried to obtain some concessions, and was partially successful. Once the Open Door policy was internationally accepted, Foreign Office again made it a fundamental element of its Chinese policy.